2023
DOI: 10.3390/catal13020274
|View full text |Cite
|
Sign up to set email alerts
|

In-Depth Kinetic Modeling and Chemical Analysis for the Epoxidation of Vegetable Oils in a Liquid–Liquid–Solid System

Abstract: A heterogeneous catalyst for producing epoxidized vegetable oils, an important intermediate in the production of non-isocyanate polyurethanes, is essential for product separation and for decreasing the side-reaction, i.e., ring-opening reaction, via the Prileschajew method. The development of reliable kinetic models considering key variables for both phases and the mass transfer phenomena is missing in the literature. The reaction pathway for the ring-opening reaction is also under debate. Therefore, we studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Conversely, the selectivity was strongly affected and decreased along the molar ratio increment. Similarly, Cai et al, 120,121 Dinda et al 52 and Mungroo et al 122 have found that an excessive hydrogen peroxide-to-double bond molar ratio leads to an increasing formation of byproducts, thus impairing the oxirane yield, independently from the acid catalyst. Conversely, the carboxylic acid is required in a lower quantity, as it acts as the oxygen carrier between the oil and aqueous phases, and after the epoxidation reaction, it is regenerated and migrated back in the aqueous phase where it can react with hydrogen peroxide again.…”
Section: Epoxidation Processesmentioning
confidence: 91%
See 3 more Smart Citations
“…Conversely, the selectivity was strongly affected and decreased along the molar ratio increment. Similarly, Cai et al, 120,121 Dinda et al 52 and Mungroo et al 122 have found that an excessive hydrogen peroxide-to-double bond molar ratio leads to an increasing formation of byproducts, thus impairing the oxirane yield, independently from the acid catalyst. Conversely, the carboxylic acid is required in a lower quantity, as it acts as the oxygen carrier between the oil and aqueous phases, and after the epoxidation reaction, it is regenerated and migrated back in the aqueous phase where it can react with hydrogen peroxide again.…”
Section: Epoxidation Processesmentioning
confidence: 91%
“…Herein the approach could be the same as for the cases in the presence of either a homogeneous catalyst or an autocatalytic mode, where a pseudo-homogeneous kinetic model can be considered. 119,121,145,146,154,182,198 The different approaches applied in the modeling of such a system are briefly discussed below.…”
Section: Triphasic Kinetic Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the epoxidation, GPC chromatograms of ECSO and ECSO-FAME show a shift of the main peak to a higher molecular weight region, implying that the ring-opening/elimination side-products are in a low extent. A secondary peak that can also be observed in both ECSO and ECSO-FAME are ascribed to oligomers resulting from ring-opening/cationic polymerization reactions [35]. The oligomer production from ECSO and ECSO-FAME is similar, but the three-armed star structure of ECSO could allow a higher availability of access to the unsaturated groups.…”
Section: Gpc Analysismentioning
confidence: 92%